Effectiveness of art-based distraction in reducing pain and anxiety of hospitalized children during cannulation procedure: A randomized controlled trial - Sherzad Khudeida Suleman; Akram Atrushi; Karin Enskär (Belitung Nursing Journal, 2022)
Background: Peripheral venous cannulation (PIVC) is one of the most common needle procedures associated with the therapies of pediatric patients, which causes pain and anxiety in children. Trace Image and Coloring for Kids-Book (TICK-B) is one of the arts-based interventions to relieve pain and anxiety, but none of the existing studies use the TICK-B to decrease children’s pain intensity and anxiety levels during PICV. Objective: This study aimed to investigate the effectiveness of the Trace Image and Coloring for Kids-Book (TICK-B) in decreasing children’s pain and anxiety during PIVC. Methods: A parallel, randomized, double-blind controlled trial was used in this study. Children aged 6–12 years were randomly allocated to one of two groups: intervention or control. The intervention group (n = 48) received the TICK-B during the PIVC, compared to no intervention in the control group (n = 52). The children, their parents, and an observer nurse rated outcomes 1-2 min after completion of the procedure. The patients in both groups were similar in age, gender, duration of hospitalization, injections, mother’s age, and education. Faces Pain Scale-Revised (FPS-R), Children’s Fear Scale (CFS), and Visual Analog Scale (VAS) were used to measure pain and anxiety. Paired and independent t-tests were used for data analysis. Results: Patients in the intervention group reported significantly reduced pain levels than those in the control group (p <0.001), as reported by children (3.08 vs. 7.06), parents (3.08 vs. 7.13), and the observer nurse (3.06 vs. 7.13), respectively. Anxiety levels were also significantly lower among patients in the intervention group than in the control group (p <0.001), as reported by children (0.88 vs. 3.17), parents (0.94 vs. 3.19), and the observer nurse (0.85 vs. 2.94), respectively. Conclusions: TICK-B is an effective technique for reducing children’s pain and anxiety during PIVC. TICK-B is a simple, inexpensive, and effective technique that nurses can use to decrease the levels of pain and anxiety of pediatric patients during intravenous cannulation.